c-Src Increases the Sensitivity to TKIs in the EGFR-Mutant Lung Adenocarcinoma - Min, Weili; He, Chenyang; Zhang, Shuqun; Zhao, Yang (Frontiers in Oncology, 2021)
c-Src and epidermal growth factor receptor (EGFR) are key apical kinases that governs cell responses to microenvironmental cues. The potential of c-Src to affect EGFR-related signaling and targeted therapy remained elusive. Initially, phosphorylated Caspase-8 at tyrosine 380 by c-Src predominantly enhanced c-Src activation to facilitate metastasis through attaining epithelial-mesenchymal transition (EMT) phenotype in lung adenocarcinoma. Mechanistically, the linkage of c-Src SH2 domain with phosphotyrosine 380 of Caspase-8 and SH3 domain with “PDEP” motif of Caspase-8 overactivated c-Src as compared with other c-Src-partner proteins. c-Src was incapable of triggering EGFR-related signaling reflected by the levels of phophotyrosine 1068, 1086 and 1145 that had no impacts on c-Src activation. Tyrosine kinase inhibitors (TKIs) suppressed EGFR-related signaling to yield cell deaths of lung adenocarcinoma by both necroptosis and intrinsic apoptosis. Given that c-Src activation was frequent in lung adenocarcinoma, blocking c-Src activation through dasatinib was able to seal the survival-signaling-related phosphotyrosines of EGFR by its SH2 domain, in turn to increase the antitumor activity of TKIs in the EGFR-mutant lung adenocarcinoma. Collectively, c-Src inactivation by dasatinib administration sensitized EGFR-mutant lung adenocarcinoma to TKIs.